Modeling Diabetes Mellitus Prevalence in West Java Using Negative Binomial Regression - Elaiya Najla Oasis; Nasywa Firdausi Chandra; Taskya Prianggita Alfinayah; Abdul Azis Abdillah; Restu Arisanti (PT Anugrah Teknologi Kecerdasan Buatan, 2026)
Diabetes Mellitus is a disease with a high number of sufferers in Indonesia. According to the West Java Provincial Health Office, the number of people with Diabetes Mellitus in West Java Province in 2022 reached 644,704 cases. The causative factor of Diabetes Mellitus is obesity, one of the triggers is food intake. Foods consisting of carbohydrates, protein, saturated fat, sugar, and fat in general can increase blood glucose levels and increase the risk of diabetes. This study aims to determine the role of food in the prevalence of Diabetes Mellitus in West Java. The method used was negative binomial regression analysis. The results obtained show that the level of consumption of fruits and vegetables, oils and fats, and nuts has a significant influence on the prevalence of Diabetes Mellitus in West Java. Public awareness to implement good eating behavior is very important to reduce the prevalence of Diabetes Mellitus in West Java.